Experimental investigation of a superconducting switch at millimetre wavelength - Tan, B; Yassin, G; Otto, E; Kuzmin, L (IEEE, 2015)
We present preliminary measured responses of a planar superconducting on/off switch operating at millimeter wavelengths. The superconducting switch, comprising three niobium nitride (NbN) bridges, is deposited across the slotline section of a back-to-back unilateral finline. The transmission characteristics of the superconducting switch illuminated by a millimeter source was measured using a superconductor-insulator-superconductor (SIS) tunnel junction as direct detector. The NbN bridges were switched from the superconducting state to the normal state by passing current through the bridges with magnitude that exceeds its critical current value. With this arrangement, we have measured a typical switching dynamic range of approximately 10 dB across the 205–240 GHz band, with the highest dynamic range of $sim$20 dB at 230 GHz. This demonstrated the successful operation of the multiple NbN bridges as a planar superconducting on/off switch.